Study of deposit accumulation and tribological degradation in diesel engine utilizing blend fuels - Faheem Ahmed Solangi; Altaf Alam Noonari; Fayaz Hussain; Zhou Ding; Bo Zhang; Luqman Razzaq (Energy Conversion and Management: X)
Utilizing alcohol in diesel engines offers an alternative approach to reducing dependence on diesel fuel. Specifically, higher alcohols such as n-butanol (nB) and n-pentanol (Pn), which have high carbon content and are largely derived from non-edible sources, can be directly blended with diesel. These blends present significant economic and environmental advantages, making the study of high-carbon alcohol use in diesel engines increasingly important. This research focused on creating blends of waste cooking oil and n-pentanol with diesel fuel, preparing three binary and ternary mixtures: DF95WCO5 and DF65WCO20Pe20. The primary goal was to investigate the fundamental characteristics of these blends. However, challenges such as increased deposits, pollutant emissions, and reduced engine performance when using biodiesel have been noted. A detailed evaluation of combustion chamber deposit buildup and its impact on emissions and engine performance was carried out. The study employed diesel, waste frying oil, and n-pentanol blends. After 200 h of operation, engine injectors and pump pistons were examined using scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) analysis. It was discovered that waste cooking oil binary mix fuel had a greater rate of carbon deposition generation than diesel fuel, with 89.68% for WCO and 80.01% for D100. By contrast, engine part deposition was reduced when n-pentanol was mixed with waste cooking oil as opposed to diesel fuel, with a deposition rate of 47.90% for n-pentanol. The results revealed notable surface structure changes on pistons with DF95WCO5 and n-pentanol blends. Wear debris concentration was reduced when using emulsified fuels, particularly in binary blends, while the ternary blend DF65WCO20Pe20 showed further reductions in Cadmium (Cd), Iron (Fe), Copper (Cu), and Nickel (Ni) compared to pure diesel. The engine demonstrated lower viscosity and increased density when operated with these blended fuels. Experimental findings highlighted significant differences between biodiesel derived from used and fresh cooking oils, including reduced engine performance, higher carbon deposits, and accelerated metal degradation in key components of diesel engine lubricating oil.